Buterfly Species Diversity and Abundance in Taraba State College of Agricultural Science and Technology, Jalingo Taraba State, Nigeria - Garkida, David Musa; David, Delphine Leila; Emmanuel, Allahnanan; Danjuma, Tsintop Bishi; Fred, Ernest Wayas (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Butterflies are in the order Lepidoptera, which are insect with scaled wings. Over 28,000 species of butterflies exist in the world today contributing to one-quarter of all named species on the earth. Lepidoptera is important to man and the health of the environment. Butterflies play a significant role in the pollination of crops and as aesthetics. The study assessed the diversity and abundance of butterfly species in the Taraba State College of Agricultural Science and Technology, Jalingo, Nigeria. Line transects were used to survey two study sites within the School using handheld sweep nets in January to March, 2024. Data were analyzed using descriptive statistics. A total of 1,153 individuals representing 21 butterfly species belonging to 3 families were recorded across the two study sites. Out of these, members belonging to the family Lyceanidae were the most csommon with 6 species being recorded accounting for 46.2% of the total species and 93.2% of total number of individuals collected in engineering complex while members belonging to the family Nymphalidae were the most common with 10 species being recorded accounting for 52.6% of the total species and low in the total number of individuals with 37.8% collected in staff quarters. Species richness, evenness and diversity varied from study sites to sites (R= 2.7014 – 2.0293), (e= 0.6691 – 0.6317), (H1= 1.9700 – 1.6203). It was recommended that management effort towards conservation be put in place so as to ensure sustenance of butterflies and ecosystem services derived from them, and further exploration of butterfly species be done to update this checklist.